2007
DOI: 10.1177/156482650702800101
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status in Postconflict Afghanistan: Evidence from the National Surveillance System Pilot and National Risk and Vulnerability Assessment

Abstract: Improving nutritional status requires a multipronged approach, directly targeting malnutrition, coupled with economic growth, household livelihood security, social protection, access to public health services, and water and sanitation. Nutrition policy, programming, and monitoring need to reflect the immediate and underlying causes of malnutrition. Future research needs to be designed to quantify the relative contribution of underlying causes of poor nutrition, allowing practitioners to prioritize responses ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…To avoid confusion, a standardized terminology of these recommendations has been proposed by a group of experts of the United Nations University (UNU), in collaboration with the Food and Agriculture Organization (FAO), the World Health Organization (WHO), and the United Nations Children’s Fund (UNICEF). The expert group proposed to use the Nutrient Intake Values (NIVs) as a common set of terms and definitions in all countries [24,25,26,27]. The NIVs encompass the following terms: the Average Nutrient Requirement (ANR), the Individual Nutrient Level (INL x ), and the Upper Nutrient Level (UNL) (Figure 1) [28].…”
Section: Methodsmentioning
confidence: 99%
“…To avoid confusion, a standardized terminology of these recommendations has been proposed by a group of experts of the United Nations University (UNU), in collaboration with the Food and Agriculture Organization (FAO), the World Health Organization (WHO), and the United Nations Children’s Fund (UNICEF). The expert group proposed to use the Nutrient Intake Values (NIVs) as a common set of terms and definitions in all countries [24,25,26,27]. The NIVs encompass the following terms: the Average Nutrient Requirement (ANR), the Individual Nutrient Level (INL x ), and the Upper Nutrient Level (UNL) (Figure 1) [28].…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have focused on the post-conflict period where vulnerabilities and risk factors can persist or be substantially different. The nutritional studies in postconflict settings that we could identify focused mainly on children <5 years of age [10,[14][15][16][17][18][19]. To ensure healthy populations of post-conflict settings, a better understanding of the magnitude and risk factors for adult malnutrition is therefore needed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence from the National Surveillance System Pilot Study and National Risk & Vulnerability Assessment [11] conducted on behalf of the Afghanistan Government, NGO's and UN in Afghanistan 2003-4, showed that in the survey area, up to 9.17% of children aged 6-59 months met the criteria for severe or moderate acute malnutrition.…”
Section: Nutrition In Childrenmentioning
confidence: 99%